Analisis Pemenuhan Standar Aflatoksin Terhadap Produktivitas Ekspor Komoditas Pala Indonesia Ke Uni Eropa - Lyra Mardiana Safitri; Yumna Adhi Sajida; Jasmine Chiarra Al Nasywa (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
In this research, we analyze compliance with aflatoxin standards on the productivity of Indonesian nutmeg exports to the European Union. This study examines previous journals that have topics relevant to the topic being studied, sourced from Google Scholar. We use a methodology that includes literature study, data and information collection, and data analysis. The results of this research show that a country's commodity export volume, whether positive or negative, is influenced by food safety regulations. In addition, we found that difficulties in fulfilling these standards still frequently occur, indicating that the requirements cannot be met by Indonesian nutmeg farmers or exporters. In the context of this research, we take the example of Indonesian nutmeg commodities exported to the European Union. We analyze the steps that can be taken so that the nutmeg commodity can penetrate the European Union market and its relationship to the productivity of nutmeg exports to the European Union so that it can reach its maximum point. The difficulty in fulfilling this standard shows that the conditions cannot be met by Indonesian nutmeg farmers or exporters. From this research, we conclude that the productivity of Indonesia's nutmeg commodity exports to the European Union needs to be carried out by meeting the food safety standards set by the European Union, especially the aflatoxin content which refers to European Commission Regulation (EC) No.1881/2006. In addition, we suggest increasing the productivity of Indonesian nutmeg exports to the European Union by ensuring product quality and meeting European Union import standards.